Społeczno-ekonomiczne uwarunkowania migracji na europejskim rynku pracy - Gubernat, Ewa (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
The phenomenon of migration is something new in Poland in the context of making decisions by Poles concerning their future. As a consequence, many of them settle abroad in search of a better life. In fact, never before Poland experienced such large scale emigration. This is a perfect investigative area for both sociologist and economists. The phenomenon might cause important socioeconomic problems. Relocation influences among others the unemployment rate, human capital supply chain, financing of social security system etc. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1191, s. 119-129